Менеджмент взаимоотношений с клиентами как инструмент банковского маркетинга (Путеводитель предпринимателя, 2020)
Relations management in unstable conditions of banks after the financial crises is an effective tool of banking marketing. The recommendations for practical usage of relations management are given for attracting and retaining clients of a bank. The effectiveness of these activities is proved.